PEDOT-Based Conducting Polymer Actuators - Hu, Faqi; Xue, Yu; Xu, Jingkun; Lu, Baoyang (Frontiers in Robotics and AI, 2019)
Conductive polymers, particularly poly(3,4-ethylenedioxythiophene) (PEDOT) and its complex with poly(styrene sulfonate) (PSS) (i.e., PEDOT:PSS), provide a promising platform to developing for soft actuators or artificial muscles. To date, PEDOT-based actuators are available in the field of bionics or biomedicine, smart textiles, microactuator and other functional applications. In comparison to other conducting polymers, PEDOT provides higher conductivity and chemical stability, lower density and operating voltages, and by dispersing of PEDOT with PSS is further enriches performances in solubility, hygroscopicity, processability and flexibility making them is advance in actuator areas. In our view, nevertheless, the actuator fabricated by PEDOT and PEDOT:PSS is still in its infancy with many unknowns and challenges that requested more comprehensive understanding for their current and future developments. This review is aimed to provide a comprehensive understanding in the actuation mechanisms, performance evaluation criteria, processing technologies and configurations, and the recent progress of materials development and applications, as well as future opportunities for improving and exploiting of PEDOT-based actuators are also elaborated.